Engineering Mathematics volume- IV : for the students of the 4th semester (CSE & IT) - Pal, B.K (U.N. Dhar & Sons, 2020)
Engineering Mathematics volume- IV : for the students of the 4th semester (CSE & IT) / Pal, B.K.. -- Kolkata: U.N. Dhar & Sons, 2020 510 P153e9v4 9th ed Rev No. of Copies : 1